Profiling the responses of soccer substitutes: A review of current literature - Hills, S. P.; Barwood, M. J.; Radcliffe, J. N.; Cooke, C. B.; Kilduff, L. P.; Cook, C. J.; Russell, M. (Sports Medicine, 2018)
Depending upon competition regulations, the laws of soccer allow between three and an unlimited number of substitutions that can be made on either a permanent or rolling basis. Substitutes are typically introduced to minimise/offset the effects of fatigue, alter tactics, replace players deemed as underperforming or injured, and/or give playing time to youth players or to squad members returning from injury. While the match-day practices of substitutes include participation in the pre-match warm-up, and sporadic periods of rewarm-up activity, it is currently unclear as to whether these pre-entry preparations facilitate optimal match performance thereafter. Acknowledging the contextual factors that possibly influence substitutes` performance, this review summarises the presently available literature on soccer substitutes, and makes recommendations for future research. Literature searching and screening yielded 13 studies, which have typically focused on characterising: (1) the patterns, including timing, of substitutes` introduction; (2) indices of match-performance; and (3) the emotional experiences of soccer substitutes. The majority of substitutions occur after the first-half has ended (i.e. at half-time or during the second-half), with introduced players exceeding the second-half physical performances of those who started the match. Observations of progressive improvements in running performance as playing time increases, and findings that substitutes mostly experience negative emotions, highlight the potential inadequacies of pre-match preparations, and present future research opportunities. Additional work is therefore needed to confirm these findings and to determine the efficacy of current preparation strategies, thereby providing opportunities to assess then address substitutes` pre-pitch entry preparations, on-field performance and emotional responses.